2019
DOI: 10.1177/1357034x19886925
|View full text |Cite
|
Sign up to set email alerts
|

Personalized Medicine in Practice: Postgenomics from Multiplicity to Immutability

Abstract: This article explores the ways in which predictive information technologies are used in the field of personalized medicine and the relations between this use and how patients and disease are perceived. This is examined in a qualitative case study of a personalized cancer clinical trial, where oncologists made clinical decisions for each patient based on drug matchings and efficacy predictions produced by bioinformatic technologies and algorithms. I focus on personalized practice itself, as a postgenomic phenom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…A comparative study with oncologists, cardiologists and family doctors concluded that oncologists felt better informed, were more able to interpret test results and more confident in discussing the results with their patients [ 27 ]. Nevertheless, even among oncologists there seems to be some uncertainty at times regarding the choice of the right treatment [ 28 , 31 ] and the interpretation [ 30 32 ] or explanation [ 31 ] of genomic data. Another exception of better knowledge was also demonstrated among clinical geneticists and genetic counsellors.…”
Section: Resultsmentioning
confidence: 99%
“…A comparative study with oncologists, cardiologists and family doctors concluded that oncologists felt better informed, were more able to interpret test results and more confident in discussing the results with their patients [ 27 ]. Nevertheless, even among oncologists there seems to be some uncertainty at times regarding the choice of the right treatment [ 28 , 31 ] and the interpretation [ 30 32 ] or explanation [ 31 ] of genomic data. Another exception of better knowledge was also demonstrated among clinical geneticists and genetic counsellors.…”
Section: Resultsmentioning
confidence: 99%
“…Our analysis adds to their work by foregrounding how the targeted trial design, which has been hailed as a ‘paradigm shift’ (Tan et al, 2009), rests on the selection of very specific patients, who we term ‘precision patients’. Other scholars have examined how genetic patient screening shapes drug development (Keating & Cambrosio, 2014; Nelson et al, 2014), the organisation of scientific and clinical practice (Cambrosio et al, 2018; Chorev, 2020), and how cancer patienthood is developing in the context of molecular information (Day et al, 2017; Kerr et al, 2021). Building on these important scholarships on experimental oncology, our analysis of patient selection illuminates how precision—even in the context of universal cancer care—comes at the cost of patient exclusion.…”
Section: Resultsmentioning
confidence: 99%
“…The human genome project, which began in 1990 to analyze the entire human sequence, was declared complete in April 2003 after 13 years and a budget of approximately US$3 billion [ 1 3 ]. The world then entered the post-genomic era, and expectations grew for the development of “personalized medicine,“ in which genomic information is applied to medical treatment [ 4 6 ]. When the 454 Genome Sequencer 20 (GS20), the first next-generation sequencing (NGS) technology, was introduced in 2005, genetic analysis using NGS became actively pursued.…”
Section: Introductionmentioning
confidence: 99%